ASSOCIATION BETWEEN MAJOR HISTOCOMPATIBILITY COMPLEX ALLELES AND SCLEROSIS MULTIPLEX IN PATIENTS FROM MACEDONIAN POPULATION - Hristova-Dimcheva, Anita; Antova, Emilija; Boskovski, Bojan; Bojadzieva Stojanoska, Biljana; Trpkovska, Biljana (Journal of Morphological Sciences, 2024)
Major Histocompatibility Complex (MHC) is a complex of genes situated in the Human Leukocyte Antigen - HLA regia which define the individuality of each unit. The alleles or molecules of this system, HLA class 1 and class 2, participate in the process of recognizing, processing and presenting of antigens which in turn activates the organism’s immunological defense. This system has an important role in tissue and organ transplantation, in relation to and predisposition for certain diseases. It is known that there is a correlation between HLA molecules and MS.        Multiple Sclerosis (MS) is a frequent inflammatory disease of the central nervous system (CNS) characterized by demyelinization of axons. The disease is chronic, it attacks the cerebrum, the spinal cord and the optical nerves and is a leading cause of nontraumatic disability in the population between 20 and 40 years of age. The disease presentation varies and depends on the lesion location. The most common symptoms include motor weakness, paresthesia, problems with the eyesight, ataxia, vertigo, and headache. The generic factors have an important role in the occurrence of MS, as HLA molecules. Identification of the connection between the HLA molecules and MS in patients from the Macedonian population. This research included 132 patients with MS, and a control group comprising 852 healthy subjects. HLA typing was done for all the patients and the HLA molecules were identified. This was accomplished using a molecular method and by isolating DNA from the blood sample, amplification of DNA from the sample using polymerase chain reaction, PCR-SSR, placement of the amplicons on electrophoresis of agarose, processing of the results in relevant program, Helmberg SCORE. The results have shown association of certain HLA molecules and MS in patients from the Macedonian population. Regarding the HLA alleles and the risk for MS, it was shown that HLA-A*02 has protective role regarding MS, (P=0.00283, OR = 0.652), while HLA-A*03 is a risky allele for development of MS (P=0.0469, OR=0.49532) in relation to the control group. The allele HLA-DRB1*15 and HLA-DQB1*06 is a risky allele for development of MS (P<0.0001, OR=2.945, P<0.0001, OR=1.9878, respectively), but the allele HLA-DQB1*03 is a protective allele for development of MS (P=0.0004, OR=0.51634) in relation to the control group. The alleles HLA-A*02, HLA-B*44, HLA-DQB1*03 have protective roles for development of MS, while the alleles HLA-A*03, HLA-DRB1*15 and HLA-DQB1*06 are risky alleles for development of MS.